Do Quality Improvement Initiatives Improve Outcomes for Patients in Antiretroviral Programs in Low- and Middle-Income Countries? A Systematic Review. (15th August 2019) - Hargreaves, Sally; Rustage, Keiran; Nellums, Laura B.; Bardfield, Joshua E.; Agins, Bruce; Barker, Pierre; Massoud, M. Rashad; Ford, Nathan P.; Doherty, Meg; Dougherty, Gillian; Singh, Satvinder
Abstract : Background: There have been a range of quality improvement (QI) and quality assurance initiatives in low- and middle-income countries to improve antiretroviral therapy (ART) treatment outcomes for people living with HIV. To date, these initiatives have not been systematically assessed and little is known about how effective, cost-effective, or sustainable these strategies are in improving clinical outcomes. Methods: We conducted a systematic review adhering to PRISMA guidelines (PROSPERO ID: CRD42017071848), searching PubMed, MEDLINE, Embase, Web of Science, and the Cochrane database of controlled trials for articles reporting on the effectiveness of QI and quality assurance initiatives in HIV programs in low- and middle-income countries in relation to ART uptake, retention in care, adherence, viral load suppression, mortality, and other outcomes including cost-effectiveness and long-term sustainability. Results: One thousand eight hundred sixty articles were found, of which 29 were included. QI approaches were categorized as follows: (1) health system approaches using QI methods; (2) QI learning networks including collaboratives; (3) standard-based methods that use QI tools to improve performance gaps; and (4) campaigns using QI methods. The greatest improvements were seen in ART uptake [median increase of 14.0%; interquartile range (IQR) −9.0 to 29.3], adherence [median increase of 22.0% (IQR −7.0 to 25.0)], and viral load suppression [median increase 26.0% (IQR −8.0 to 26.0)]. Conclusions: QI interventions can be effective in improving clinical outcomes; however, there was significant variability, making it challenging to identify which aspects of interventions lead to clinical improvements. Standardizing reporting and assessment of QI initiatives is needed, supported by national quality policies and directorates, and robust research. Abstract : Supplemental Digital Content is Available in the Text.